1994
DOI: 10.7326/0003-4819-120-11-199406010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Internists' Attitudes about Clinical Practice Guidelines

Abstract: Although most ACP members studied recognized the potential benefits of practice guidelines, many were concerned about possible effects on clinical autonomy, health care costs, and satisfaction with clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
238
4
13

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(269 citation statements)
references
References 0 publications
14
238
4
13
Order By: Relevance
“…Credible, evidence-based guidelines often lack the power to change longstanding clinical practice. Physicians may view them as a threat, particularly if they are perceived as challenging their professional judgment or as compromising patient care (Tunis et al, 1994). They may also be unwilling to forgo personal practice style and may resist the guideline's implementation.…”
Section: Implementing Depression Guidelines In Primary Carementioning
confidence: 99%
“…Credible, evidence-based guidelines often lack the power to change longstanding clinical practice. Physicians may view them as a threat, particularly if they are perceived as challenging their professional judgment or as compromising patient care (Tunis et al, 1994). They may also be unwilling to forgo personal practice style and may resist the guideline's implementation.…”
Section: Implementing Depression Guidelines In Primary Carementioning
confidence: 99%
“…Self-administered surveys of Canadian 10 and American 11,12 internists have found that familiarity with guidelines varies depending upon guideline type; subspecialists are more familiar with guidelines developed by their specialty organizations. [10][11][12] Some clinicians believe that guidelines are an oversimplified approach to medicine, are too rigid to apply to individual patients, and challenge physician autonomy.…”
Section: Conclusion : De Nombreuses Institutions Canadiennes Dévelop-mentioning
confidence: 99%
“…[10][11][12] Some clinicians believe that guidelines are an oversimplified approach to medicine, are too rigid to apply to individual patients, and challenge physician autonomy. [10][11][12] A recent systematic review found that many physicians perceive guidelines as difficult to use and confusing, and that guideline format is often a major barrier to use. 13 The foregoing data may not apply in the ICU setting.…”
Section: Conclusion : De Nombreuses Institutions Canadiennes Dévelop-mentioning
confidence: 99%
“…18,49,50 Other variables measured include knowledge, skills, decision-making, and barriers to guideline use. 49,[51][52][53] Four recent articles 49,[52][53][54] described the use of a randomized control trial to evaluate these variables. One study 54 used a quasiexperimental method, and 5 studies used a survey method to evaluate outcome variables related to practice guidelines.…”
Section: Measurement Of Multiple Variablesmentioning
confidence: 99%
“…One study 54 used a quasiexperimental method, and 5 studies used a survey method to evaluate outcome variables related to practice guidelines. 18,51,[55][56][57] . Each study in this category used a selfreport questionnaire to explore the variables under consideration after the dissemination of practice guidelines.…”
Section: Measurement Of Multiple Variablesmentioning
confidence: 99%